nfluência dos parâmentros físico-químicos nas propriedades e na produção de biossurfactantes isolados do gênero cândida - Silva, Patricia Andrea Cordeiro da (2011)
Studies on the production of biosurfactants by yeasts were performed, considering the biotechnological potential and the large number of publications with Candida yeasts, anamorph state. Based on these data was performed with the yeast Candida lipolytica, state anormofo, evaluations to clarify the influence of chemical and physical parameters (pH. agitation, cultivation time and medium composition), associated with carbon sources (soluble and insoluble) and nitrogen on the production of emulsifying agents, and chemical composition of the polymers. In this sense, the behaviors of four strains of C.lipolytica from Culture for Collection were evaluated, with the variable response emulsification activity and chemical composition of the emulsifiers. The profile of the constituent fatty acids of vegetable oils used in fermentation processes was established as: saturated, monounsaturated and polyunsaturated. Initial evaluation was done with the carbon source glucose, indicating two distinct groups of biosurfactants chemical structure was influenced by carbon source concentration (1 and 1.5%). In the use of babassu oil (high level of saturated fatty acids) as carbon source was observed three distinct profiles in terms of speed of agitation and time of fermentation, consisting of: Protein- Carbohydrate-Lipids and Carbohydrate-Protein-Lipids. However, the nitrogen source was changed the formation of the complex Protein-Carbohydrate-Lipids. The use of vegetable oils, and hydrocarbon refinery residue, allowed the formation of three groups, where only the hydrocarbon polymer formed a constitution just for carbohydrates and proteins. The other complexes were formed consisting of Proteins-Lipids- Carbohydrates. Therefore, studies showed the direct influence of the carbon/nitrogen / sources,and agitation with the metabolic aspects of the production of biosurfactants. Thus, the profiles described here related to the chemical structure of biosurfactants produced by Candida lipolytica, anamorph state, suggest the stability of the structure, using industrial waste, reducing the process of costs production, the efficiency as substrate and low cost, and the excellent emulsifying properties, surface tension reduction, biodegradability and biocompatibility